Tourism and Hospitality Essentials (THE) Journal, Vol.II, No.2, 2012 - 315 PENGARUH SHOPPING DESTINATION STRATEGY TERHADAP KEPUTUSAN BERKUNJUNG DI WISATA BELANJA MALL (Studi Banding pada Pengunjung Wisata Belanja Mall Kota Bandung yang terdiri dari Mall Cihampelas Walk dan Mall Paris Van Java) - Mardiyana, Eva; Wibowo, Lili Adi; Andari, Rini (Universitas Pendidikan Indonesia, 2012)
Bandung is one of the main destinations as shopping malls tourism, such as Cihampelas Walk and Paris Van Java Mall. Cihampelas walk and Paris Van Java are not only providing places for family to do shopping, playing and culinary area. The presence of Cihampelas Walk and Paris Van Java Mall is expected to increase interest in visitors to visit the shopping malls in Bandung. But the lack of visitor’s interest to visit shopping malls in Bandung reflects a problem in shopping malls in Bandung so it needs some programs to increase visitor’s interest to visit by maximize the shopping destination strategy. This research objectives are to find out about the implemented shopping destination strategy, decision to visit, and the impact of shopping destination strategy to decision to visit and the difference of the implementation of shopping destination strategy to decision to visit in Cihampelas Walk and Paris Van Java Mall. The theory of shopping destination strategy is from Kotler and Armstrong. The research object is the visitors of Cihampelas Walk and Paris Van Java Mall. This research is using descriptive, comparative and verification research. The method is explanatory survey with stratified random sampling as sampling technique, 400 respondents (160 respondents in Cihampelas Walk and 240 respondents in Paris Van Java Mall). The data analysis technique is path analysis with SPSS 18 as the computer software. The data collection techniques are interviews, and questionnaire distribution. The finding of this research is there an impact of shopping destination strategy which consists of location, shopping venue design display layout on decision to visit. The dimension of shopping destination strategy which has the highest influence is shopping venue design and the one with the lowest influence is display layout. While the most appealing factor of decision to visit is the brand. Suggestion to these companies is to maximize its shopping destination strategy in order to increase the interest to visit shopping malls in Bandung.